Impact of HLA compatibility on lung transplant survival and evidence for an HLA restriction phenomenon: a collaborative transplant study report - Opelz, Gerhard; Süsal, Caner; Ruhenstroth, Andrea; Döhler, Bernd (Transplantation, 2010)
Background. - Data concerning the impact of human leukocyte antigen (HLA) compatibility on lung transplant survival rates are limited. - Methods. - Using the Collaborative Transplant Study database, 5-year graft outcome according to HLA mismatch was examined in 8020 deceased donor lung transplants performed during 1989 to 2009. - Results. - Graft survival rates showed a stepwise decrease as the combined number of HLA-A+B+DR mismatches increased from one to six (P<0.001). Surprisingly, the 28 grafts with 0 mismatches at all 3 loci had a 1-year survival rate of only 49.7%, significantly lower than for 1, 2, 3, 4, 5, or 6 mismatches (P=0.002, <0.001, <0.001, <0.001, 0.002, and 0.003, respectively). Multivariate regression analysis confirmed that, paradoxically, transplantation of grafts with zero HLA-A+B+DR mismatches was associated with a 19% increase in relative risk of failure. Donor lung preservation for up to 12 hr was not associated with inferior graft survival versus shorter preservation times (P=0.60). - Conclusions. - Our data show that a high number of HLA mismatches or zero mismatches impacts unfavorably on lung transplant survival.